Masail Fiqiyah Kontemporer dalam Penggunaan Media Sosial di Kalangan Mahasiswa (Kajian terhadap Perilaku Bermedia Sosial Mahasiswa Berdasarkan Al-Qur'an, Hadis, dan Kaidah Fikih) - Silvi Yumnita; Ayu Hana; Alya Tri Nurmala Sari; Tsamrotul Amaliah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
The development of information technology has significantly increased the use of social media, especially among university students. Social media serves not only as a means of communication but also as a space for self-expression, information exchange, and identity formation. However, uncontrolled use of social media has raised various contemporary Islamic legal issues (masail fiqhiyah), including ghibah (backbiting), the spread of hoaxes, cyberbullying, riya (showing off), and violations of privacy. This study aims to identify and analyze various masail fiqhiyah arising from social media use among students and to examine their legal status from the perspective of Islamic jurisprudence. This study employs a qualitative approach with a descriptive-analytical method through library research. The findings of the study indicate that various activities on social media have the potential to violate Islamic legal principles when they are not accompanied by ethical awareness and adequate legal understanding. Therefore, the implementation of Islamic ethical values, such as tabayyun (verification), guarding one's speech, and moral responsibility, is essential in using social media. This study is expected to contribute to the development of contemporary fiqh studies and serve as a guideline for students in using social media wisely and in accordance with Islamic teachings. Keywords: Contemporary Fiqh, Islamic Ethics, Masail Fiqhiyah, Social Media, Students